Using variable costing to support product pricing and achieve profitability – a case study at the General Company for Pharmaceutical Industries and Medical Supplies – Samarra (The International Journal for Scientific Research, 2025)
This study aims to explore the effectiveness of using the variable costing method in supporting product pricing and enhancing profitability, while analyzing its role in improving the company’s financial and managerial decisions. Monthly and annual production and cost data of the products were analyzed using a descriptive-analytical approach to determine the impact of variable costing on pricing and profitability. The study population included all products and production lines of the company during the specified period, with a focus on a sample of the most produced and best-selling products for detailed analysis. The results indicated that the application of the variable costing method significantly contributes to improving pricing strategies and increasing profitability, while also enhancing management’s ability to make more effective and flexible financial decisions. Based on the findings, the study recommends reinforcing the adoption of the variable costing method as a basis for pricing decisions, alongside continuous monitoring and analysis of production data to ensure optimal financial outcomes and maximize the company’s economic value.
Keywords: Variable Costing; Product Pricing; Profitability